2023
DOI: 10.1021/acs.jpclett.3c00912
|View full text |Cite
|
Sign up to set email alerts
|

NMR Relaxation Experiments Probe Monomer–Fibril Interaction and Identify Critical Interacting Residues Responsible for Distinct Tau Fibril Morphologies

Abstract: Tau aggregation is governed by secondary processes, a major pathological pathway for tau protein fibril propagation, yet its molecular mechanism remains unknown. This work uses saturation transfer and lifetime line-broadening experiments to identify the critical residues involved in these secondary processes. Distinct residue-specific NMR relaxation parameters were obtained for the truncated three repeat tau construct (K19) in equilibrium with structurally different, self-aggregated (saK19) or heparin-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“… ,, The relaxation studies on the C322A construct confirm the absence of mutual interactions of the two motifs in the monomeric form. In our recent study, we observed that Δ R 2 profiles of 3R tau in the presence of tauAD and tauCTE seeds showed similar Δ R 2 profiles for these two motifs as observed in this study . Thus, based on the Cryo-EM structure and our NMR relaxation studies, we propose that the modulation dynamics of 321 KCGS and 364 PGGGN motifs will shape the final structure of AD/CTE filaments.…”
Section: Resultssupporting
confidence: 86%
“… ,, The relaxation studies on the C322A construct confirm the absence of mutual interactions of the two motifs in the monomeric form. In our recent study, we observed that Δ R 2 profiles of 3R tau in the presence of tauAD and tauCTE seeds showed similar Δ R 2 profiles for these two motifs as observed in this study . Thus, based on the Cryo-EM structure and our NMR relaxation studies, we propose that the modulation dynamics of 321 KCGS and 364 PGGGN motifs will shape the final structure of AD/CTE filaments.…”
Section: Resultssupporting
confidence: 86%
“…The participation of the R1 repeat in templated aggregation was also observed in recent studies of K19 Tau (R1R3R4TH6) constructs from our laboratory. 50 The inferences from NMR aggregation studies were corroborated by using ThT fluorescence measurements (Figure S6) under the same NMR experimental conditions. GG construct shows accelerated kinetics with a half-time (t 1/2 ) of 12.5 days compared to WT (t 18 1/2 days) thereby showing that the NMR studies probed aggregation at the early stages.…”
Section: Time-dependent Aggregation Studies To Identify the Aggregati...mentioning
confidence: 68%
“…53,66 The involvement of R1 repeat in aggregation supports its part in promoting fibril formation, as recently demonstrated in our laboratory. 50 Results from NMR experiments that probed backbone conformations, such as average amide chemical shift differences and secondary structure propensities, reveal that the residues of the AIM are perturbed due to the G326E mutation. Further, the changes in backbone conformation at the G326E mutation site significantly impact the local dynamics at the AIM, as evidenced by the pronounced differences in relaxation rates of 317 KVTSKCGS 324 segment.…”
Section: Time-dependent Aggregation Studies To Identify the Aggregati...mentioning
confidence: 99%
See 1 more Smart Citation